Chromosome-level genome assembly of a xerophytic plant, Haloxylon ammodendron. (10th March 2022) - Wang, Mingcheng; Zhang, Lei; Tong, Shaofei; Jiang, Dechun; Fu, Zhixi
Abstract: Haloxylon ammodendron is a xerophytic perennial shrub or small tree that has a high ecological value in anti-desertification due to its high tolerance to drought and salt stress. Here, we report a high-quality, chromosome-level genome assembly of H. ammodendron by integrating PacBio's high-fidelity sequencing and Hi-C technology. The assembled genome size was 685.4 Mb, of which 99.6% was assigned to nine pseudochromosomes with a contig N50 value of 23.6 Mb. Evolutionary analysis showed that both the recent substantial amplification of long terminal repeat retrotransposons and tandem gene duplication may have contributed to its genome size expansion and arid adaptation. An ample amount of low-GC genes was closely related to functions that may contribute to the desert adaptation of H. ammodendron . Gene family clustering together with gene expression analysis identified differentially expressed genes that may play important roles in the direct response of H. ammodendron to water-deficit stress. We also identified several genes possibly related to the degraded scaly leaves and well-developed root system of H. ammodendron . The reference-level genome assembly presented here will provide a valuable genomic resource for studying the genome evolution of xerophytic plants, as well as for further genetic breeding studies of H. ammodendron .